Evaluación de la contaminación acústica producida por el tráfico vehicular en la ciudad de Ibarra - Espinosa Lima, Pablo Andrés (2018)
The present investigation contemplates the analysis of noise pollution by mobile sources such as vehicular traffic in the city of Ibarra, it is important to indicate that by using georeferenced computerized systems such as ArcGIS, Google Maps and OpenStreetMap, a noise map will be proposed that I evaluated Predictively the behavior of public and private transit and transport of the city through the CadnaA simulation software. To collect data, it was essential to adapt the behavior of the city's automotive park in the study of noise through the counting of vehicular traffic, in the most critical points of the city. Where they will be analyzed thanks to the simulation software. According to the study, Ibarra is still a city with low vehicular noise levels in most of its parishes, but by increasing the annual number of vehicles, these noise levels will increase exponentially, according to the time.